2003
DOI: 10.1002/eji.200324115
|View full text |Cite
|
Sign up to set email alerts
|

Functional CD25 and CD25+ mucosal regulatory T cells are induced in gut‐draining lymphoid tissue within 48 h after oral antigen application

Abstract: Oral antigen application induces tolerance, leading to suppression of a subsequent systemic challenge with this antigen. The suppression is mediated by mucosal regulatory T (Tr) cells that may differentiate from naive peripheral T cells in the gut-draining lymphoid tissue. However, little is known about the initial steps of this differentiation process. In this study we show that 48 h after oral OVA treatment, antigen-specific T cells in mesenteric lymph nodes (MLN) and Peyer's Patches (PP) were activated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
109
0
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(117 citation statements)
references
References 42 publications
4
109
0
4
Order By: Relevance
“…Of importance, and consistent with a recent report by HauetBroere et al (25), we found that in addition to the strong induction of CD25 ϩ CD4 ϩ T reg , i.g. treatment with OVA/CTB conjugate also induced CD25 Ϫ CD4 ϩ T cells that displayed suppressive function both in vitro and in vivo after adoptive transfer of these highly purified cells in recipients immunized s.c. with OVA/CFA.…”
Section: Discussionsupporting
confidence: 93%
“…Of importance, and consistent with a recent report by HauetBroere et al (25), we found that in addition to the strong induction of CD25 ϩ CD4 ϩ T reg , i.g. treatment with OVA/CTB conjugate also induced CD25 Ϫ CD4 ϩ T cells that displayed suppressive function both in vitro and in vivo after adoptive transfer of these highly purified cells in recipients immunized s.c. with OVA/CFA.…”
Section: Discussionsupporting
confidence: 93%
“…In models of orally fed Ag, both mesenteric LNs and Peyer's patches were shown to be the predominant sites of Ag presentation (58 -61), and critical for the induction of oral tolerance (59,62). To a lesser extent, oral Ag delivery has also been shown to induce clonal expansion of Ag-specific T cells in the spleen and, in cases in which high doses of Ag are administered, even in peripheral LNs (61,63,64). In our study, only very minute populations of donor transgenic T cells underwent proliferation in distal LNs.…”
Section: Discussionmentioning
confidence: 99%
“…OVA-TCR transgenic T cells were isolated and labeled, as described previously (10,11). Briefly, at 8 -12 wk of age, DO11.10 transgenic mice were sacrificed, and LN and spleens were collected.…”
Section: Kinetics Of Ova-specific T Cell Response In Vitro and In Vivomentioning
confidence: 99%
“…Recently, we have shown that mucosal Tr are highly discriminative, suppressing inflammatory responses exclusively to the Ag used for tolerization and expanding their suppressive capacity by infectious tolerance (9). These mucosal Tr differentiate from naive CD4 ϩ T cells in the mucosa-draining lymphoid tissue within 72 h post-Ag application and reside in both CD25 ϩ as well as CD25 Ϫ subsets (10,11). The precise mechanisms underlying the induction of mucosal Tr and subsequent development of tolerance are the focus of extensive research that may yield important clues on the development of selective immunomodulatory therapies for T cellmediated inflammatory diseases, ranging from autoimmunity to transplant rejection and allergy.…”
mentioning
confidence: 99%